Preclinical evaluation of the antipsychotic potential of the mGlu2‐positive allosteric modulator JNJ‐40411813. Issue 2 (30th January 2015) - Lavreysen, Hilde; Langlois, Xavier; Donck, Luc Ver; Nuñez, José María Cid; Pype, Stefan; Lütjens, Robert; Megens, Anton
Abstract: JNJ‐40411813/ADX71149 (1‐butyl‐3‐chloro‐4‐(4‐phenylpiperidin‐1‐yl) pyridin‐2(1H)‐one) is a positive allosteric modulator (PAM) of the mGlu2 receptor, which also displays 5‐Hydroxytryptamine (5HT2A ) antagonism after administration in rodents due to a rodent‐specific metabolite. JNJ‐40411813 was compared with the orthosteric mGlu2/3 agonist LY404039 (4‐amino‐2‐thiabicyclo [3.1.0] hexane‐4, 6‐dicarboxylic acid 2, 2‐dioxide), the selective mGlu2 PAM JNJ‐42153605 (3‐(cyclopropylmethyl)‐7‐(4‐phenylpiperidin‐1‐yl)‐8‐(trifluoromethyl)[1, 2, 4]triazolo[4, 3‐a]pyridine) and the 5HT2A antagonist ritanserin in rodent models for antipsychotic activity and potential side effects, attempting to differentiate between the various compounds and mechanisms of action. In mice, JNJ‐40411813, JNJ‐42153605, and LY404039 inhibited spontaneous locomotion and phencyclidine‐ and scopolamine‐induced but not d‐amphetamine‐induced hyperlocomotion; the 5HT2A antagonist ritanserin inhibited only spontaneous locomotion and phencyclidine‐induced hyperlocomotion. As measured by 2‐deoxyglucose uptake, all compounds reversed memantine‐induced brain activation in mice. The two mGlu2 PAMs and LY404039, but not ritanserin, inhibited conditioned avoidance behavior in rats. Like ritanserin, the mGlu2 ligands antagonized 2, 5‐dimethoxy‐4‐methylamphetamine‐induced head twitches in rats. LY404039 but not the mGlu2 PAMs impaired rotarod performance in rats and increased the acoustic startle response in mice. Our results show that although 5HT2A antagonism has effect in some models, mGlu2 receptor activation is sufficient for activity in several animal models of antipsychotic activity. The mGlu2 PAMs mimicked the in vivo pharmacodynamic effects observed with LY404039 except for effects on the rotarod and acoustic startle, suggesting that they produce a primary activity profile similar to that of the mGlu2/3 receptor agonist while they can be differentiated based on their secondary activity profile. The results are discussed in light of clinical data available for some of these molecules, in particular JNJ‐40411813. Abstract : e00097